The gastrointestinal system - an essential target organ of the athlete`s health and physical performance - Berg, A.; Miller, H. M.; Rathmann, S.; Deibert, P. (Exercise Immunology Review, 1999)
An athlete`s ability to reach maximum performance is a direct result of physical and muscular performance, muscular and systemic stress tolerance, control and regulation of immune function, and adaptation to physical stress. In this complex sense, the gastrointestinal (GI) tract is also part of the system that controls and regulates adaptation and regeneration of the athlete. A well-balanced GI immune system and an optimized immune competence may protect the athlete from harmful pathogens; it may also protect against dietary as well as inhaled antigens. However, under conditions of mechanical and biochemical stress, the integrity of the GI mucosal block, particularly the epithelial hood, can be damaged, leading to a pathological uptake of toxic or immunogenic substrates. This may occur in endurance athletes, since gut symptomatology, nausea, vomiting, pain, bloating, diarrhea, cramping, and bleeding can be observed in up to half of all participants in endurance events. In addition, composition of stool and fecal microflora in endurance athletes has shown that there may be a specific need for nutritional support for mucosal immunity in highly trained but chronically stressed athletes. Proper diet during training and competition is a significant factor in guarding against GI symptoms and exercise-induced gastrointestinal side effects that may compromise immune competence and physical performance. The present review presents some important suggestions on the possible role of the GI tract in human performance and stress tolerance, and offers new insights about the influence of food quality on the immune system of the gut.